Some Biochemical Parameters of Pisum sativum Extracted with Lactobacillus lactis - Guvenc, Ayse Nilay; Kirbag, Sevda (Asian Journal of Chemistry, 2013)
This study analyzed the effects of inulin containing Pisum sativum on Lactobacillus lactis. In the study, fatty acid flavonoid reseratrol content, vitamin, phytosterol levels and the animicrobial activites of P. sativum and the fatty acid, flavonoid, resveratrol content, vitamin, phytosterol levels and animicrobial activites of L. lactis extracts treated with P. sativum were determind and compared. For this purpose, the control (P. sativum), L. lactis treated with P. sativum (Ps+LI) and L. lactis only cultures (LI) were used. According to experimental results the fatty acid and vitamin levels of the P. sativum extracts significantly increased after being treated with L. lactis significatly increased whereas in the controls that the flavonoid and reservatrol levels decreased while the antimicrobial activity showed variations.
Keywords: Probiotic bacteria; Prebiotic; L. lactis; Pea